Development of an IREC Learning Model Based on Reliable Practices to Boost the Character Achievement of Elementary Students - Mulyawati, Ismuningsih; Dewantoro, M. Hajar; Joko Susilo, Mohamad (International Journal of Learning Reformation in Elementary Education, 2024)
The character crisis of elementary school students since online learning during the COVID-19 pandemic requires Islamic education teachers to improve the quality of learning models that can boost character achievements. This research aims to determine the factors that influence the development of the IREC model and the quality of the IREC model. IREC is the subject matter of Islamic Religious Education and Character. This development research uses the Research and Development model with the stages of definition, design, development, and dissemination. Data collection techniques include interviews, questionnaires, and documentation as well as Focus Group Discussions. Qualitative descriptive data analysis techniques are carried out by analyzing, describing, and summarizing events from data obtained through the interview process, documentation, and observation. The research results show that the success of implementing the IREC model is influenced by supporting factors, namely competent Islamic education teachers, active participation of students, and material moral support from the Principal, Teachers, and parents. The inhibiting factor is the lazy attitude of students. The reliable practice-based IREC model has met the quality of feasibility based on assessments by material and media experts and has been feasible in wide-scale testing. The implementation of the reliable practice-based IREC model can increase the achievements of religious character, responsibility, honesty, discipline, tolerance, and independence.